Dampak Penggunaan Gadget Terhadap Perkembangan Bahasa Anak Kelas I Sekolah Dasar - Silvia Meirisa (Peneliti.net, 2023)
This 4.0 era where gadgets are part of children's games that are difficult to separate in their daily activities. Using ganget makes children experience problems in language development, especially in the aspects of listening and speaking skills. The influence of the use of gadgets has a major impact on children's language development where there are some children who prefer to be quiet and interact less during the learning process in classroom. When the teacher explains the learning, it seems that the student does not participate in answering questions from the teacher. The purpose of this study was to determine the influence of gadget use on language development, especially in the aspects of listening and speaking for grade 1 elementary school children. This research was conducted in November 2022 at SDN 51/XI Kumun Mudik. The Sample in this study were 30 grade 1 elementary school students. This research used quantitative research using correlation research methods. The instrument used was in the form of a questionnaire of questions that were distributed to parents and teachers. The results of this study stated that there is a relationship between the use of gadgets as a whole and children's language development. Thus, the strength of the relationship is not very strong, with a negative correlation direction-0.024 which means that the use of gadgets is related and affects the child's language development. If the use of gadgets increases in children, the value of children's language development also decreases and vice versa if the use of gadgets decreases, the child's language development increases at SDN 51/XI Kumun Mudik, Kumun Debai District, Sungai Penuh City, Jambi Province.